ANALISIS SIKAP DAN PERAN TUGAS KESEHATAN DENGAN PENGGUNAAN AKSEPTOR METODE KONTRASEPSI JANGKA PANJANG - Riski, Merisa (JURNAL KESEHATAN TERAPAN, 2021)
The target of the Family Planning (KB) program is to control population growth and increase quality of small families. This is one of the efforts to prevent the increasing rate of population growth. To achieve this target, several policy directions have been formulated, one of which is an increase in the use of contraceptives that are more effective and efficient in the long term. Objective: to determine the relationship between maternal attitudes, and the role of health workers simultaneously with long-term contraceptive method acceptors (MKJP). This type of research is quantitative using analytical survey methods, namely surveys or research that tries to explore how and why health phenomena occur with a "Cross Sectional" approach where the independent variables (mother's attitudes, the role of health workers) and the dependent variable are Acceptors of Long-Term Contraceptive Methods. . The sampling technique used in this study is Stratified Random Sampling or random sampling. The sample in this study amounted to 76 people. The results showed that there was a relationship between mother's attitude (p-value 0.00, p<0.05), and the role of health workers (p-value 0.002, p<0.05) with the use of long-term contraceptive method acceptors. Conclusion: The relationship between mother's attitude and the role of health workers simultaneously with Long-Term Contraception Method Acceptors (MKJP).Keywords: Attitude, Role of Health Officers, Use of Family Planning Acceptors